2015
DOI: 10.1136/annrheumdis-2014-206580
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based provisional clinical classification criteria for autoinflammatory periodic fevers

Abstract: The objective of this work was to develop and validate a set of clinical criteria for the classification of patients affected by periodic fevers. Patients with inherited periodic fevers (familial Mediterranean fever (FMF); mevalonate kinase deficiency (MKD); tumour necrosis factor receptor-associated periodic fever syndrome (TRAPS); cryopyrin-associated periodic syndromes (CAPS)) enrolled in the Eurofever Registry up until March 2013 were evaluated. Patients with periodic fever, aphthosis, pharyngitis and aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(165 citation statements)
references
References 30 publications
3
146
0
16
Order By: Relevance
“…Осуще-ствлялись попытки выявления каких-либо мутаций у паци-ентов с СЮА, они представлены в отдельных зарубежных публикациях, а в России пока эксклюзивны [12][13][14]. Экс-пертами в области изучения АВЗ для их идентификации предложены алгоритмы диагностики, включающие клини-ческие классификационные критерии, рекомендации по лечению [15][16][17][18][19]. Разработаны также диагностический счет для определения степени риска наличия АВЗ и показания для проведения молекулярно-генетического анализа [20].…”
Section: с о в P E м е н н а я р е в м а т о л о г и я № 3 ' 1 7 о р unclassified
“…Осуще-ствлялись попытки выявления каких-либо мутаций у паци-ентов с СЮА, они представлены в отдельных зарубежных публикациях, а в России пока эксклюзивны [12][13][14]. Экс-пертами в области изучения АВЗ для их идентификации предложены алгоритмы диагностики, включающие клини-ческие классификационные критерии, рекомендации по лечению [15][16][17][18][19]. Разработаны также диагностический счет для определения степени риска наличия АВЗ и показания для проведения молекулярно-генетического анализа [20].…”
Section: с о в P E м е н н а я р е в м а т о л о г и я № 3 ' 1 7 о р unclassified
“…Periodic fever is frequently accompanied by other symptoms such as abdominal pain, arthralgia, and sometimes arthritis, myalgia, and signs specific for the respective disorder. However, there is great variation among individuals with the same mutations even within one family, and fever can be irregular, rare, or absent altogether even when there are other symptoms of severe inflammation [6][7][8]. Amyloidosis is a possible severe complication of most of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The patient fulfilled the Eurofever clinical diagnostic/classification criteria for TRAPS. 4 Genetic testing revealed that the child carried heterozygous mutations in two autoinflammatory genes: C30Y in the TNFRSF1A gene and K695R in the MEFV gene. For a few years, febrile attacks accrued every eight to 10 weeks and were well-controlled with short, intermittent courses of oral steroids.…”
Section: Case Reportmentioning
confidence: 99%